INFECTIVE ENDOCARDITIS – THE REVIEW - Skrzypek, Weronika; Skrzypek, Szymon; Gąbka, Rafał; Stępniak, Karol; Kaźmierczyk, Aleksandra; Kęsik, Jędrzej; Madycka, Daria; Słaboń, Małgorzata; Zdybel, Michał; Rdzanek, Bartłomiej Józef (International Journal of Innovative Technologies in Social Science, 2026)
Infective endocarditis (IE) is a serious and potentially life-threatening infection that affects the endocardium, heart valves, or implanted cardiac devices. It can present with a broad range of nonspecific symptoms, making early diagnosis difficult. The condition is typically confirmed through the detection of bacteremia and various imaging techniques, such as echocardiography, computed tomography (CT), and nuclear imaging. These tests can reveal anatomical changes or areas of altered metabolism, particularly on the heart valves or around foreign materials, such as prosthetic valves or cardiac devices. Treatment of IE generally involves a combination of antibiotic therapy and, in some cases, surgical intervention, with the decision for surgery depending on the patient’s evolving clinical status. Over time, the epidemiology of IE has shifted, largely due to the increasing use of prosthetic valves and implantable devices, resulting in a higher incidence among older patients with multiple comorbidities. Historically, Streptococci and Enterococci were the primary causative organisms, but recent trends show a rise in infections caused by Staphylococci species and non-HACEK organisms. The management of IE requires early recognition, tailored antibiotic therapy, and timely surgical intervention when necessary. A multidisciplinary approach involving cardiologists, infectious disease specialists, and surgeons is essential for optimal care, given the complexity and high mortality associated with the condition. This review highlights the evolving epidemiology, diagnostic approaches, and treatment strategies for IE, emphasizing the importance of early detection and coordinated care.